Schubert: Die schöne Müllerin - Youens, Susan (Cambridge Cambridge University Press, 1992)
This is a guide to both the music and the poetry of Schubert's much-loved song cycle, set to poems by the Prussian poet Wilhelm MÜller. Composed in 1823, this work is one of the greatest masterpieces of the song repertoire. The genesis of both the poetry and the music, composed soon after Schubert discovered that he had contracted syphilis, is discussed in the first two chapters. A chapter on the poetry considers MÜller's uneasy relationship to the tenets of Romanticism; the influence of Goethe, folk poems, and medieval poetry on Die schöne MÜllerin; and a reading of each of the poems, which are reproduced in German and in English translation. The final chapter provides commentary on each of the twenty songs in the cycle.